What can Expeditions do for Students … and for Science? An Investigation into the Impact of University of Glasgow Exploration Society Expeditions. Issue 1 (2nd January 2017) - Harper, Lynsey R.; Downie, J. Roger; Muir, Martin; White, Stewart A.
ABSTRACT: The benefits of field courses for biological science students are well established, but field courses also have limitations: they are generally too brief to allow significant research and they are staff-designed and led, limiting the development of student autonomy. In contrast, the value of student-organised field expeditions has been little researched. Here, as a case history, we analyse students' attitudes to their experience of being selected for and taking part in University of Glasgow Exploration Society expeditions. Students regarded taking part in an expedition as one of the best things they had done in their life thus far. Expeditions were excellent value for money, provided opportunities to develop transferable skills (fund-raising, budgeting, report production, composing and delivering oral and written presentations, team-working and leadership, negotiation with stakeholders from different cultures) and provided scope for fieldwork skill development and substantial, publishable research. Participants also believed the expeditions provided real benefits to the communities visited. Participation in expeditions can contribute to each student's Higher Education Achievement Report.